THU0005 An immunochip based interrogation of scleroderma susceptibility variants. (23rd January 2014) - Charlesworth, J.; Stankovich, J.; Lewis, P.; Byron, J.; Stevens, W.; Sahhar, J.; Proudman, S.; Roddy, J.; Nash, P.; Tymms, K.; Brown, M.; Zochling, J.
Abstract : Background: Understanding the genetic architecture of scleroderma (SSc) susceptibility is vital both in gene discovery and in determining the influence of previous identified susceptibility variants. Objectives: To perform an immunochip-based interrogation of scleroderma susceptibility variants using cases from the Australian Scleroderma Cohort Study. Methods: We selected 557 cases from the Australian Scleroderma Cohort Study for genotyping with the Immunochip, a custom Illumina Infinium genotyping array containing 196, 524 rare and common variants shown to be important in a wide variety of autoimmune disorders. 4, 537 controls were taken from the 1958 British Birth cohort. Genotype data were analysed with PLINK. Samples and SNPs with low call rates were excluded, as were SNPs in Hardy-Weinberg disequilibrium or with less than two occurrences of the minor allele. Eigenstrat was used to analyze population structure. The final dataset consisted of 505 cases, 4, 491 controls and 146, 867 SNPs. Allelic association analyses were conducted using Fisher's exact test. Genotype clusters were manually examined for all associations of p<10 -5 since calling is difficult for some rare variants. Results: Significant and suggestive associations were detected at seven loci. Several of these have been previously implicated in scleroderma susceptibility ( HLA-DRB1 and STAT4 ) and several are novel associations, including SNPs near PXK (p=4.4×10 -6 ) and CFDP1 (p=2.6×10 -6 ). The strongest associations were with SNPs in the class II region of the MHC. One of the most strongly associated SNPs (rs4639334; p=1.6'10 -8 ; OR=1.8) is in linkage disequilibrium ( r 2 =0.46) with the class II allele HLA-DRB1*11:01 . This allele has been associated with SSc. Another strongly associated SNP is rs2857130 (p=1.6'10 -8 ; OR=0.67), which lies in the promoter region of HLA-DRB1, but is not in LD with any classical MHC alleles. Outside the MHC, there were six regions of association with p<10 -5, including the confirmed SSc locus at STAT4 . Several SNPs implicate a locus at PXK, which has been previously associated with systemic lupus erythematosus (SLE) but not with SSc. The remaining associations are novel for both SSc and SLE and require replication. Of particular interest is a rare variant located within a non-coding RNA on chromosome 6q21 which was approximately 20 times more frequent in cases than controls. We are currently dissecting the potential biological implications of this locus. Conclusions: This pilot study has confirmed previously reported SSc associations, revealed further genetic overlap between SSc and SLE, and identified putative novel SSc susceptibility loci including a rare allele with major effect size. Disclosure of Interest: None Declared